Spatial and Temporal Variation in the Occurrence and Abundance of the Freshwater Turtles in Water Bodies of a Peri-Urban Area in the Midwestern Brazil - Elizângela Silva de Brito; NICOLLE B. F. PRADO; KLYSMAN F. F. ALMEIDA; LUCIANA M. VALÉRIO; Christine Strüssmann; Tainá F. Dorado-Rodrigues (Acta Herpetologica)
In this study we evaluated spatial and temporal variations in the occurrence and abundance of freshwater turtles in four water bodies located in the headwaters of a stream in the peri-urban area of Campo Grande, Mato Grosso do Sul, Midwestern Brazil. Over the 38 months sampled between 2014 and 2017, we captured 94 individuals: 73 of Phrynops geoffroanus, 19 of Mesoclemmys vanderhaegei, and two of Trachemys dorbigni. The probability of detecting individuals of Mesoclemmys vanderhaegei increased with the occurrence of rainfall, while for Phrynops geoffroanus probability increased with increasing temperature. The abundance of both species varied between water body types, with Phrynops geoffroanus being more abundant in larger water bodies only in the first year of sampling. The abundance of both species was highest during the rainy season between November and March. Despite the syntopic occurrence of Phrynops geoffroanus and Mesoclemmys vanderhaegei, the occurrence of the former influenced the occurrence and abundance of the latter species, thus presenting different patterns over time and space.